MEMBANGUN UNIVERSITAS BERBASIS PONDOK PESANTREN - Muzadi, Hasyim (STAI Ma'had Aly Al-Hikam Malang, 2013)
The development of modern education requires Muslims to revitalize Islamic education system, both institutional and scientific structure. Institutionally, Indonesian Muslims have a unique system of educational institutions which is different from common boarding school in general, namely Pesantren. Pesantren education system when combined with the University system (faculty of several different sciences under one roof), can be proposed as a pilot project to develop a universal science; without religion-science dichotomy based on Tawheed paradigm (unity) in accordance with Qur 'anic education theory.